2000
DOI: 10.1136/bmj.321.7259.477
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1995 pill scare on rates of venous thromboembolism among women taking combined oral contraceptives: analysis of General Practice Research Database

Abstract: Objective To compare the incidence of venous thromboembolism among women taking combined oral contraceptives before and after the October 1995 pill scare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 14 publications
(10 reference statements)
0
44
1
Order By: Relevance
“…Although the statement noted that "for the vast majority of women, the pill is safe," some subsequent research suggested that it was followed by a spike in conceptions and abortions without a decrease in venous thromboembolism incidence among pill users. 32,33 Replication of this sad experience in the United States should be avoided.…”
Section: Do the Current Product Labels Adequately Reflect The Risk-bementioning
confidence: 94%
“…Although the statement noted that "for the vast majority of women, the pill is safe," some subsequent research suggested that it was followed by a spike in conceptions and abortions without a decrease in venous thromboembolism incidence among pill users. 32,33 Replication of this sad experience in the United States should be avoided.…”
Section: Do the Current Product Labels Adequately Reflect The Risk-bementioning
confidence: 94%
“…Essentially two research teams used different methods to investigate this question and drew opposite conclusions from the same dataset -in this case the GPRD. (Farmer et al 2000) found the incidence of venous thromboembolism did not fall following the 1995 'pill scare' and subsequent reduction in pill use, whilst (Jick et al 2000) re-analysed the data and contested that the risk with third generation preparations was around twice that of those containing levonorgestrel. Whilst Farmer et al (2000) used a time correlation study, Jick et al (2000) used a cohort plus nested case-control designs, controlling extensively for potential confounders and including a time correlation approach for comparison.…”
Section: Iv) Data On Outcomes May Not Reflect the Priorities Of Servimentioning
confidence: 99%
“…Moreover, the authors of one of the prompting studies corroborated their findings in a follow-up analysis, 22 whereas one group of the faultfinders was found in the Bpillory[ themselves because of methodological deficiencies in presenting the same data set in a different way, leading to a different conclusion. 23 This raised the issue of appropriate conduct of (pharmaco-)epidemiological research. 24,25 One wonders if the quality of epidemiological studies can be improved so that confusing debates are reduced.…”
mentioning
confidence: 99%